A Simple Microfluidic Integrated with an Optical Sensor for Micro Flow Injection Colorimetric Determination of Glutathione - Supharoek S.-A. (2014)
A simple and inexpensive method for fabricating a microfluidic platform was developed. A printed circuit board (PCB) was used to make a master mold for replicating a polydimethylsiloxane (PDMS) microchannel. The master mold was fabricated by a simple photolithographic method, employing a photoresist dry film. The process did not use hazardous chemicals, a clean room or any expensive instrument. The PDMS microchannel was clamped with polymethylmethacrylate (PMMA) plates, where a light emitting diode (LED) as a light source and a light dependent resistor (LDR) as a light sensor were attached to form a simple optical sensor. The system was successfully employed as a micro flow injection analysis for the determination of glutathione in dietary supplement samples. A linear calibration graph in the range of 5.0-60.0 mg L -1 glutathione was obtained with a detection limit of 0.01 mg L -1. The system provided a sample throughput of 48 h -1, with microliter consumption of the reagent. © The Japan Society for Analytical Chemistry.